In the Honour of Tristram Engelhardt, Jr.: On the Sources of the Narrative Self - Motzkin, Gabriel (Conatus - Journal of Philosophy, 2018)
Modern philosophy is based on the presupposition of the certainty of the ego’s experience. Both Descartes and Kant assume this certitude as the basis for certain knowledge. Here the argument is developed that this ego has its sources not only in Scholastic philosophy, but also in the narrative of the emotional self as developed by both the troubadours and the medieval mystics. This narrative self has three moments: salvation, self-irony, and nostalgia. While salvation is rooted in the Christian tradition, self-irony and nostalgia are first addressed in twelfth-century troubadour poetry in Occitania. Their integration into a narrative self was developed in late medieval mysticism, and reached its fullest articulation in St. Teresa of Avila, whom Descartes read.